PENGENTASAN KEMISKINAN MODEL MUHAMMAD YUNUS - Dimyati, - - (Irtifaq, 2014)
Muhammad Yunus, known as His bank Grameen program is an economist who holds a Ph.D. Yunus was a man who rebelled against the economic theories has. Poverty alleviation programs Yunus is the Grameen Bank, which is lending to the poor while minimizing the risk that these resources will be wasted. Grameen Bank is not based on compassion or generosity, because this way can not help them out of poverty. Even generosity will destroy them, because they will always depend on the mercy of others. Grameen Bank in lending actually based on a commercial relationship with the provision of motivation to work hard and honestly. At Grameen Bank, Yunus only provide micro-credit to the people who want to try, it means capital provided is used for working capital. Yunus believes there are no poor people who want to live in constant poverty they also want to live a decent, it's just that they need capital to prove his worth. Keyword: Poverty Alleviation, Muhammad Yunus, Grameen Bank